Tinjauan Yuridis Normatif oleh Dittipidter Bareskrim Polri Terhadap Tindak Pidana Illegal Logging Sebagai Upaya Penanggulangan Kasus Eksploitasi Sumber Daya Kehutanan - Andika, Rulli Jeremy; Sri Handayani, Riska; Muriman, Chairul (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The purpose of this scientific research article is to analyze the normative juridical review of illegal logging crimes by the Dittipidter Bareskrim Polri, to examine the elements contained in illegal logging crimes in cases of forestry resource exploitation, and to find out the efforts that can be made by the Dittipidter Bareskrim Polri as a follow-up to handling criminal acts of illegal logging in order to minimize the occurrence of cases of forestry resource exploitation. In this research, classical law enforcement theory is used. The research method used is qualitative with a normative juridical approach. The results of the research show that the normative juridical review of illegal logging criminal acts by the National Police's Criminal Investigation Directorate refers to the P3H Law no. 18 of 2013. The elements contained in the criminal act of illegal logging in cases of exploitation of forestry resources, namely increasing population, changing the function of forestry areas to other land, changing the function of mangrove forests into ponds, lack of understanding of land ownership and use of natural resources, non-synchronization of PP No. 21 of 1970 regarding the forest exploitation system, availability of wood raw materials, environmental pollution around industry and agriculture in forests, population transmigration, lack of coordination between parties, and weak law enforcement. Efforts that can be carried out by the Dittipidter Bareskrim Polri include restructuring the wood processing industry, cooperative management of law enforcement regarding the exploitation of forestry resources, operations to secure forest areas on an ongoing basis blended learning, wildlife inter-regional enforcement, identifying building blocks or strategies for a holistic approach around emerging technologies in policing, the wildlife trafficking cybercrime program, dan training on development of suspects profiles (wildlife crime).